SENAM HIPERTENSI TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DI WILAYAH KERJA PUSKESMAS BONTONYELENG - Zatul Haefa; Hamdana; Amirullah (Jurnal Kesehatan Panrita Husada, 2019)
Elderly is the final stage of development in the human life cycle. In the elderly there is an anatomic decline and function of the organs. Decreased function of blood vessels can cause hypertension. Hypertension or high blood pressure is a condition where when the blood pressure in the blood vessels increases, the measurement results are 140/90 mmHg. One that affects the reduction in hypertension without drugs is exercise that is not too heavy on a regular basis such as hypertension gymnastics. Hypertension or elderly exercise is a form of aerobic exercise that is beneficial for the elderly. Regular elderly exercise can help maintain blood pressure balance. The purpose of this study was to determine the effect of hypertension exercise on reducing blood pressure in the elderly in the work area of ​​the Bontonyeleng Health Center. The design of this study used a pre-experimental research design (One-group pre-post test design) obtained a sample of 30 people by using a sampling technique that is Nonprobability sampling with incidental sampling approach. The results of the normality test show that the data are not distributed so that they do not meet the paired T test and an alternative test is used is the Wilcoxon test. P value obtained is 0,000 (p <0.05) on systolic and diastolic blood pressure, so Ho is rejected and Ha is accepted. It can be concluded that there is an effect of hypertension gymnastics on the decrease in systolic and diastolic blood pressure in the elderly in the work area of ​​the Bontonyeleng Health Center. And it is advisable to have information about hypertension and further increase the frequency of exercise in the elderly at least 2-3 times a week to get better results.